Understanding interpatient variation of clinical responses among acute lymphoblastic leukaemia (All) patients treated with 6-mercaptopurine (6-Mp): a pharmacogenomics-metabolomics perspective / Wan Rosalina Wan Rosli - Wan Rosli, Wan Rosalina (Institute of Graduate Studies, UiTM, 2012)
Leukaemia chemotherapy had advanced considerably, enabling higher rates of survival and cure. This success is largely attributable to optimization of the use of chemotherapeutic agents such as 6-mercaptopurine (6-MP). However challenges still remain in striking a delicate balance between therapeutic outcome and risk of toxicity due to the narrow therapeutic window of anticancer drugs. This is compounded by the variability in patient response even when given the standard dose. Identification of patients at risk of adverse events would be beneficial, thus pharmacogenomics could play a role in reducing the related adverse drug reaction and hospitalization by the development of diagnostic tools to tailor appropriate therapies for patients.